Framing Media Jawa Pos Radar Kudus dalam Pemberitaan Keracunan Progam Makan Bergizi Gratis di SMAN 2 Kudus - Syuhada' Muhammad Syuhada'; Mas’udi Mas’udi (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Media coverage of government programs is rarely a neutral act; it is always shaped by the editorial values, institutional interests, and sociopolitical environment of the outlet producing it. This study examines how Jawa Pos Radar Kudus framed its coverage of the food poisoning incident linked to the Free Nutritious Meal (Makan Bergizi Gratis/MBG) program at SMAN 2 Kudus in January 2026, an event that placed both a national food security initiative and local governance under public scrutiny. Adopting a qualitative approach grounded in the constructivist paradigm, this research applies Robert N. Entman’s four-element framing model define problems, diagnose causes, make moral judgement, and treatment recommendation to five news articles published between January 29 and February 7, 2026. The analysis reveals that Radar Kudus constructed a critical-constructive frame, acknowledging the failures of technical implementation while consistently protecting the MBG program itself from systemic policy criticism. The local government was persistently portrayed as a responsive authority, while recommended solutions pointed exclusively toward internal system improvements rather than program discontinuation.